Pengaruh Kualitas Pelayanan dan Bauran Pemasaran terhadap Kepuasan Pasien Rumah Sakit Lira Medika Karawang - Angga, Aditya; Syaodih, Erliany; Rachman, Arif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
At the beginning of its development, the hospital was an institution that functioned for social purposes, but with the existence of private hospitals, the institution was more referred to as an industry engaged in the field of health services by carrying out management based on business entity management. As a business entity, hospitals must be able to create loyalty from patients. The aim of creating patient loyalty is that hospitals can provide a medical experience, improve service quality, and survive in intense competition between hospitals. This research aims to determine the effect of service quality and marketing mix on patient satisfaction at Lira Medika Karawang Hospital. This research uses quantitative methods, explanatory positivistic approach, and cross sectional study design. The population in this study were 9,496 patients. The sample was selected based on random sampling technique with 100 patients. Data collection is done by filling out a questionnaire. Data analysis techniques were carried out using univariate, bivariate and multivariate methods with linier regression. The research results show that partially service quality has a positive and significant effect on patient satisfaction. Marketing Mix has a positive and significant effect on patient satisfaction. Service quality and marketing mix simultaneously have a positive and significant effect on patient satisfaction at Lira Medika Hospital Karawang. The test results of coefficient of determination obtained value R2 = 0,225, meaning that the effect/contribution service quality to patient satisfaction was 22,5%. The test results of coefficient of determination obtained value R2 = 0,254, meaning that the effect/contribution marketing mix to patient satisfaction was 25,4%. The test results of coefficient of determination obtained value R2 = 0,16, meaning that the effect/contribution service quality and marketing mix to patient satisfaction was 16,0%.